Development of Quality Standards of Ammi majus L. Fruit - Md.Waris2, H.Hasan2,B.Ali2,N.Chaudhary2,M. Khan2,A. Ali2,S.Najib2,H.Farooqi3, H.N. Khan2*, Parwaiz Akhtar1, Mohd Ali2, M.P Sharma4, (Journal of Experimental Sciences, 2010)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Ammi majus Linn (Apiaceae) is an erect branching annual herb, cultivated in northern part of India mainly Jammu and Kashmir. It is commonly used in day to day life. In present investigation an attempt has been made for the pharmacognostical standardization and evaluation of Ammi majus fruit. The pharmacognostical evaluation comprises of detailed macroscopy, powdered microscopy, fluorescence analysis and physical constants such as ash and extractive values. The data obtained in present study will serve as valuable tool for identification, authentication and detection of adulterants, standardization and quality control of the drug. The developed technique will also be useful for the standardization of formulations containing A. majus.